MODEL MATEMATIKA SEIT UNTUK PENYEBARAN PENYAKIT DIABETES NON GENETIK - ADELINDRA, MERRY; LUSIANA, VINA (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
The SEIT (Susceptible-Exposed-Infected-Treatment) mathematical model for the spread of non-genetic diabetes, or type 2 diabetes, was developed to analyze the dynamics of the disease in a population. Type 2 diabetes is caused by insulin resistance and can lead to serious complications. In this model, it is assumed that the population is constant, with no genetic factors or migration, and infected individuals cannot be cured, but can receive treatment to extend their life. The SEIT model forms a system of differential equations that describes the changes within the Susceptible (S), Exposed (E), Infected (I), and Treatment (T) compartments. The model's analysis includes determining the disease-free equilibrium point, where the entire population is in the susceptible (S) compartment with no exposed, infected, or treated individuals, and the endemic equilibrium point, where all compartments maintain a balance. Stability analysis using the Jacobian matrix shows that the disease-free equilibrium is asymptotically stable. The basic reproduction number (R?) is calculated using the next-generation matrix approach and serves as an indicator of equilibrium stability. If R? ? 1, the model has only a stable disease-free equilibrium, but if R? > 1, a stable endemic equilibrium will be established. ABSTRAKModel matematika SEIT (Susceptible-Exposed-Infected-Treatment) untuk penyebaran diabetes non-genetik, atau diabetes tipe 2 dikembangkan guna menganalisis dinamika penyakit dalam populasi. Diabetes tipe 2 disebabkan oleh resistensi insulin dan dapat menimbulkan komplikasi yang serius. Dalam model ini, diasumsikan bahwa populasi bersifat konstan tanpa adanya faktor genetik atau migrasi dan individu yang terinfeksi tidak dapat sembuh, tetapi dapat menjalani perawatan untuk memperpanjang hidup. Model SEIT ini membentuk sistem persamaan diferensial yang menggambarkan perubahan dalam kompartemen Susceptible (S), Exposed (E), Infected (I), dan Treatment (T). Analisis terhadap model mencakup penentuan titik ekuilibrium bebas penyakit, yaitu ketika seluruh populasi berada dalam kompartemen rentan (S) tanpa individu yang terpapar, terinfeksi, atau dalam perawatan, serta titik ekuilibrium endemik, di mana terdapat keseimbangan di semua kompartemen. Analisis kestabilan menggunakan matriks Jacobian menunjukkan bahwa titik ekuilibrium bebas penyakit stabil secara asimtotik. Bilangan reproduksi dasar (R?) dihitung melalui pendekatan matriks generasi berikutnya dan berfungsi sebagai indikator kestabilan titik ekuilibrium. Jika R? ? 1, model hanya memiliki titik ekuilibrium bebas penyakit yang stabil, tetapi jika R? > 1, maka titik ekuilibrium endemik yang stabil akan terbentuk.